Comparative Study in the Design of a Reinforced Concrete Structure - WONG, JING XIAN; Md Noh, Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2022)
Nowadays, the application of software is popular in engineering field. This raised a problem that which software should be used in order to get the best solution.  The objectives of this study are to model a double storey reinforced concrete building using Esteem Integrated Total Solution and Tekla Structural Designer and to evaluate the structural design outputs in term of the loading analysis, structural analysis, reinforcement detailing and the taking off results. A double storey reinforced concrete integrated office building was modelled, analyzed and designed complying with the Eurocode (EC) and the Malaysian Standard (MS). The load combination was designed according to serviceability load limit state and ultimate limit state. Seismic load and wind load were not considered in this study to reduce the complexity in achieving the objectives. A double storey reinforced concrete integrated office building was modelled, analyzed and designed in Esteem and Tekla based specifications and assumptions in accordance with Eurocode (EC) and the Malaysian Standard (MS). The structural design outputs and taking off results were exported form Esteem and Tekla and compared. From this study, it was found that both Esteem and Tekla have their own strengths where Esteem resulted a more cost-effective taking off result while Tekla is more conservative, flexible and user-defined.